Exploring Neuromyths in Counselor Education: A Neuro-Informed Cognitive Behavioral Therapy Approach - James R Spears; Natasha Villalobos; Whitney Zahar-Rich; Priscilla R Prasath; WIllie Ray (Teaching and Supervision in Counseling, 2025)
Although advances in neuroscience validate the therapeutic practices and professional identity of counselors, educators struggle to infuse accurate neuroscience knowledge into the classroom. Utilizing a quasi-experimental, repeated measures design, this study examined the effectiveness of a neuro-informed lecture in reducing neuromyth endorsement among graduate students enrolled in the counseling theories course. Participants (n = 62) completed a demographics questionnaire and identical neuroscience pre- and post-surveys. The intervention group (n = 32) received the lecture-based intervention, while those in the comparison group (n = 30) did not. Results revealed significant improvement in neuroscience knowledge scores for those receiving the lecture (pre: M = 41.47, SD = 3.689; post: M = 45.25, SD = 3.203; t (31) = -4.082, p = 0.0003, Cohen’s d = -0.722), while the comparison group experienced minimal change. Findings suggest the effectiveness of lecture interventions in enhancing neuroscience understanding and reducing neuromyth endorsement in counseling theories students.
Keywords: neuromyths; neuro-informed cognitive behavioral therapy; student learning; counselor education; course lecture